How much insecurity does security need? The discrepancy in assessing the sense of security of children, adolescents, and caregivers in institutions. Issue 4 (1st October 2016) - Allroggen, Marc; Domann, Sophie; Strahl, Benjamin; Schloz, Carolin; Fegert, Jörg M.; Kampert, Meike
ABSTRACT: When developing concepts for protecting children and youth who live in institutions, the perspective of the addressees has so far been insufficiently taken into account. This study aims to compare the assessment of children, youth, and caregivers in institutions with regard to group atmosphere, participation, and sense of safety. A combined quantitative and qualitative approach compares the assessment of children or youth and caregivers in child and youth welfare institutions, boarding schools, and clinics through the use of an online questionnaire and group discussions that address the topics safety, group atmosphere, and participation. The quantitative questionnaire included 233 youth age 14 years and up and 490 caregivers; 87 children or youth between the ages of 11 and 18 years and 73 caregivers were part of the qualitative group discussion. The questionnaire showed that youth and caregivers assessed the sense of security in principle as positive. With regard to group atmosphere and participation, youth tended to see these aspects in a positive light, but almost all youth-aged participants viewed these specific categories more critically than did the adult caregivers. The results from the group discussions make clear that children, adolescents, and caregivers often underestimate the real dangers. The existing sense of security in institutions may be the result of underestimating real dangers. Implications for the implementation of protection concepts are drawn.